The Third-Year Teacher Rut (pp. 34--42) - Miller, Lesley (Ohio Journal of School Mathematics, 2019)
In this paper, I discuss a recent revelation regarding my use of Teachers Pay Teachers (TPT) lessons. I analyze falsehoods promoted by a Crime Scene Investigation (CSI) activity I downloaded from TPT and discuss ways in which the lesson unwittingly re-enforced implicit bias and stereotypes of other cultures among my students. Lastly, I explore possible revisions generated with teaching colleagues in a recent graduate-level pedagogy course.